Challenges and Perspectives on Real-time Singing Voice Synthesis - Brum, Leonardo Araujo Zoehler; Moreno, Edward David (Revista de Informática Teórica e Aplicada, 2020)
This paper describes the state of art of real-time singing voice synthesis and presents its concept, applications and technical aspects. A technological mapping and a literature review are made in order to indicate the latest developments in this area. We made a brief comparative analysis among the selected works. Finally, we have discussed challenges and future research problems.